A Study on the Relationship between Attitude Towards the Computer and Learning Strategies in Terms of Some Variables - S. Gunduz; A.A. Kurt (University of Sofia, 2011)
The aim of this study is to investigate the relationship between computer attitudes and learning strategies. Study group of the research consists of 195 candidate teachers (77 male, 118 female) from Education Faculty of Selcuk University. The research data were gathered from Computer Attitude Scale, Cognitive Learning Strategies Scale, Metacognitive Learning Strategies Scale and Personal Data Form. The research findings are: candidate teachers have medium level computer attitudes, a significant correlation between computer attitude, cognitive and metacognitive learning strategies, candidate teachers who have low computer attitude uses more cognitive and metacognitive learning strategies, male candidate teachers have higher level of computer attitudes than female candidate teachers, female candidate teachers use more cognitive learning strategies, a significant difference in cognitive learning strategies of candidate teachers' according to the type of the high school graduated.